Optimizing School Operational Assistance (Dana BOS) Management to Improve the Quality of Islamic Education in Indonesia - Ummi, Farkhatul (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2025)
Purpose – This study investigates the management strategies of the School Operational Assistance (Dana BOS) fund in Islamic schools, with a specific focus on the integration of digital financial reporting, performance-based evaluation, and auditing mechanisms to improve educational quality and accountability. Design/methods – Using a qualitative library research design, the study systematically analyzed secondary sources—including peer-reviewed journals, academic texts, and government reports—related to educational finance, Islamic school governance, and public fund accountability. Literature was selected from reputable databases and categorized using thematic coding aligned with management functions such as planning, budgeting, implementation, and evaluation. Findings – The findings indicate that Islamic schools implementing digital reporting systems, external audits, and managerial training programs demonstrate more transparent and efficient BOS fund management. The study also reveals disparities in fund utilization between urban and rural Islamic schools, influenced by infrastructure, institutional capacity, and community participation. Schools that embraced integrated governance frameworks aligned with Islamic values achieved greater educational impact. Research implications/limitations – The research is limited by its reliance on secondary data, which may not capture localized implementation challenges or informal practices within school management. Further empirical studies involving field-based data collection are recommended to validate and deepen the findings. Practical implications – Policymakers should mandate digital reporting platforms, institutionalize external audits, and invest in managerial capacity-building to enhance BOS fund governance. Stakeholder involvement through school committees is essential to promote transparency and ensure fund alignment with educational priorities. Originality/value – This study contributes to the growing discourse on Islamic education finance by offering a context-specific framework that links digital innovation, managerial ethics, and participatory oversight. It provides evidence-based recommendations that support equitable, accountable, and outcome-driven use of public education funds in religious school contexts.